PENELITIAN BRIKET KOKAS PADA TUNGKU KUPOLA DOUBLE TUYER MENINGKATAN EFISIENSI PENGECORAN LOGAM - Supriyanto, R. Herry (Badan Pengkajian dan Penerapan Teknologi, 2007)
Cupola Double Tuyer (CDT) kiln could Increase the efficiency of metal pouring.process. By using CDT coke ratio can be increasel up to 1 : 14 (1kg iron :14 kg forme coke). Tuyer has function thing air with pressure to burn formed cokes. There fase dimention of tuyer shoud be determid precisely to set up the temperature. The reach bet ween formed cokes and oxygen is exotermie wechliquidate metal